Factors affecting livelihood strategies of smallholder tobacco and non-tobacco farmers and off-farm households benefitting from land reform in Zimbabwe - Alexander Mapfumo; Abbissynia Mushunje (Wydawnictwo Uniwersytetu Przyrodniczego w Poznaniu, 2023)
The main objective of this paper was to determine the factors that affect the livelihood strategies of resettled smallholder farmers in Zimbabwe. The study was conducted in Manicaland Province in Zimbabwe, and the respondents were stratified into four groups. These were smallholder farmers resettled under the A1 and A2 models, as well as tobacco and non-tobacco smallholder farmers. The two models differ in how they were implemented and supported, which might lead to them having different livelihood strategies. A total of 300 respondents were surveyed, consisting of 114 tobacco and 149 non-tobacco farmers and 24 off-farm and 13 wage-earner households in Manicaland province. The study used a Multinomial Logit model to investigate the factors influencing a household’s decision to choose different livelihood strategies. In the model, the dependent variables included four livelihood strategies, while the explanatory variables included various household social-economic and institutional factors. The results obtained from the multinomial logistic regression model established that gender and land size were significant at a level of 1%, and education, household size, access to credit and access to inputs were significant at 5% in the adoption of tobacco farming, access to credit and gender were significant at a 1% level in the adoption of non-tobacco farming, while education was significant at a 10% level in adopting off-farm were found to be significant in determining the adoption of the tobacco farming in the study area up to less than 10% probability level in adopting off-farm activities. Smallholder farmers who did not adopt tobacco farming indicated that limited land size, shortage of labour and access to tobacco inputs were the major impediments to adopting tobacco farming. The government should support the efforts of smallholder farmers to increase their livelihood strategies through unveiling credit lines for farming activities. Access to inputs for smallholder farmers should be made a priority by the government through the provision and fair distribution of adequate agricultural inputs.